PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI STRATEGI PEMBELAJARAN JIGSAW DI KELAS IV MIN 3 KOTA BANJARMASIN - Julkifli, Muhammad; Maulida, Azkia; Azkia, Risyatul (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
Abstract: The purpose of this study is to ascertain if the jigsaw learning technique improves Indonesian language learning results in class IV MIN 3 Banjarmasin City throughout the 2023–2024 academic year. This research design provides information and facts that were known at the time the study was conducted, or it employs descriptive research with an ex post facto method. Because a test is used as a research tool in this study, it may also be classified as survey research. However, PTK is the methodology employed in this study. Students in class IV MIN 3 in Banjarmasin City served as the study's participants. Fifteen students participated in the study. Tests, interviews, and documentation were among the methods the researcher employed to gather data. Tables and graphs were used to display the descriptive analysis of the data. The study's findings demonstrated that, under the initial conditions prior to the cycle, the percentage of student learning outcomes was still 46.33 with a very low category. However, when cycle I was implemented using the jigsaw learning strategy, the percentage of student learning outcomes was 53% with a low category. In contrast, it achieved a high category of 86% in cycle II. From the starting circumstances to cycle I to cycle II, the outcomes of learning Indonesian with the jigsaw learning approach improved by 66%. The learning results of Indonesian fourth-grade students at MIN 3 Banjarmasin City can thus be enhanced by the application of the jigsaw learning technique. Keywords: Indonesian Language, Jigsaw Learning, Learning Outcomes. Abstrak: Penelitian ini bertujuan untuk menguji keefektifan metode Jigsaw dalam pembelajaran bahasa Indonesia di Kelas IV Min 3 di Kota Banjarmasin tahun ajaran 2023–2024. Penelitian ini menggunakan penelitian deskriptif dengan pendekatan ex post facto, dengan memberikan informasi dan fakta yang telah diketahui pada saat penelitian dilakukan. Penelitian ini juga dapat dikategorikan sebagai penelitian survei karena teknik penelitian yang digunakan adalah tes. Namun, penelitian ini menggunakan pendekatan PTK. Siswa kelas IV Min 3 Kota Banjarmasin berpartisipasi dalam penelitian ini. Sebanyak 15 siswa terlibat dalam penelitian ini. Data dikumpulkan melalui wawancara, dokumentasi, dan tes. Analisis data deskriptif disajikan dengan menggunakan grafik dan tabel. Berdasarkan hasil penelitian, keadaan awal sebelum siklus memiliki proporsi hasil belajar siswa yang relatif rendah yaitu 46,33. Siklus pertama dengan menggunakan teknik pembelajaran jigsaw menghasilkan 53% hasil belajar siswa dengan kategori rendah. Di sisi lain, pencapaian puncaknya terjadi pada siklus kedua dengan 86%. Teknik pembelajaran Jigsaw menghasilkan peningkatan hasil belajar Bahasa Indonesia sebesar 66% antara siklus pertama dan kedua. Siswa Kelas IV Bahasa Indonesia di Min 3 Kota Banjarmasin dapat memperoleh manfaat dari penggunaan metode pembelajaran jigsaw. Kata Kunci: Bahasa Indonesia, Hasil belajar, Strategi Pembelajaran Jigsaw.